The adoption of a virtual learning environment in a teacher education institution: the processes and tensions - Benn, Patricia J.A. (2016)
The study investigates the processes by which a teacher education institution in Antigua and Barbuda learns to use Moodle, a Virtual Learning Environment (VLE), as a tool to offer courses online. Also under investigation were the tensions inherent in this change process. The research employs elements of the Activity Theory framework proposed by Engeström, (1999) namely, the principle of multi-voicedness which gives voice to the multiple perspectives of the participants and contradictions or tensions which are inherent disturbances to understand the social system under investigation. In this qualitative research, the data were generated from multiple sources, including multiple interviews with participants, personal journal entries, and workshop evaluations. Most of the data presentation and analysis took place concurrently. The process of learning to use Moodle took place over a three year period and involved 4 main training events. The study points to the critical role of leadership in articulating a clear direction of where the institution wants to go and providing the technological and psychological support to propel the adoption. Other tensions arose as a result of the multiple initiatives to which the participants were adjusting at that time. Tensions also arose when some participants’ desire to be professional converged with limited typing and computer skills, unreliable internet service and the additional time required for designing courses for online/blended delivery. Several recommendations are made including, the need for a) clearly articulated vision, b) policies related to mandatory adoption, c) budgetary allocation, and d) assessment of the readiness of the institution to embark on the initiative.